DESKRIPSI PEMBELAJARAN TEMATIK DALAM MASA PANDEMI COVID-19 PADA SISWA KELAS IV SEKOLAH DASAR NEGERI 37 PONTIANAK TENGGARA - Prihatink, Shyntia; Halidjah, Siti; Pranata, Rio (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the implementation of thematic learning during the Covid-19 pandemic in grade IV students of the 37 Southeast Pontianak State Elementary School which refers to the Regulation of the Minister of Education and Culture No. redesigned by the Education Quality Assurance Institute (LPMP). This research is included in the descriptive type of qualitative research. The data collection technique in this study was sourced from the homeroom teacher of class IV B at the 37 Southeast Pontianak State Elementary School. Using data collection instruments in the form of interviews, observations and documentation. The data analysis used is data selection, data presentation and conclusion drawing. The results of this study indicate that the implementation of limited face-to-face learning (PTM) has been carried out quite well, teachers have prepared planning and carried out learning quite well using methods adapted to student needs during the Covid-19 pandemic. However, limited face-to-face learning also has obstacles in its implementation considering that the available learning time is very limited so that teachers must increase the provision of learning motivation to children so that understanding of the material presented during learning can be well received by students.